Optical spectrum of HDE 245770 /A0535 + 26/ - R. A. Wade; J. B. Oke (The Astrophysical Journal, 1977)
Invasive pulmonary aspergillosis (IPA) not only causes high morbidity and mortality, especially in immunocompromised patients, but also occurs in immunocompetent individuals. Differentiating infection from colonization is challenging, and bronchoalveolar lavage fluid metagenomic next-generation sequencing (BALF-mNGS) may aid diagnosis, microbiome profiling, and clinical assessment. We retrospectively analyzed patients with suspected IPA who underwent BALF-mNGS between December 2021 and March 2025. Patients were classified by immune status. IPA diagnosis was based on EORTC/MSGERC 2020 criteria in immunocompromised patients, while immunocompetent cases were adjudicated using an integrated clinical, radiological, and microbiological assessment. A total of 178 patients were finally included and classified according to immune status into an immunocompromised group (n = 77) and an immunocompetent group (n = 101). Aspergillus_ reads per ten million (RPTM) values were significantly higher in infection versus colonization cases in both groups, with optimal cut-offs of 24 (gray zone: 22-60) for the immunocompromised group and 33 (gray zone: 17-48) for the immunocompetent group. Microbiome analysis revealed distinct community structures between infection and colonization groups, with Aspergillus remaining significantly enriched after false discovery rate (FDR) correction in immunocompromised patients, while no taxa remained significant after FDR correction in immunocompetent patients. BALF-mNGS guided antifungal therapy, avoiding unnecessary treatment in colonized patients, and higher Aspergillus_RPTM was associated with increased 90-day mortality in immunocompromised patients. BALF-mNGS may accurately distinguish Aspergillus infection from colonization and reveal microbial shifts, particularly in immunocompromised patients. It can guide targeted antifungal therapy, avoid unnecessary treatment, and higher Aspergillus_RPTM was associated with 90-day mortality in immunocompromised patients, suggesting its potential value for risk stratification.IMPORTANCEBALF-mNGS with quantitative thresholds improves differentiation between Aspergillus infection and colonization. It reveals distinct lung microbiome patterns under different immune statuses, extending beyond simple pathogen detection. Higher Aspergillus burden is associated with worse outcomes in immunocompromised patients, suggesting its potential value for risk stratification.